Peran Teknologi Informasi dan Sistem Informasi Manajemen dalam Mendukung Pengambilan Keputusan Organisasi - Rabiatul Adabiah Bancin; Muhammad Irwan Padli Nasution (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The development of information and communication technology (ICT) has brought fundamental changes in the management of modern organizations. The transformation from manual systems to digital technology-based systems improves the quality of data processing and the effectiveness of managerial decision-making. Management Information Systems (MIS) have become an important instrument in providing accurate, relevant, and timely information. This article aims to examine the role of ICT and MIS in supporting organizational decision-making processes through a literature review method. The literature includes systems theory, information technology, management information systems, and decision support systems. The results of the study indicate that the implementation of ICT and MIS not only improves internal efficiency but also strengthens the organization's ability to respond to the dynamics of the business environment.